Motional Fock states for quantum-enhanced amplitude and phase measurements with trapped ions - Fabian Wolf (Nature Portfolio, 2019)
Quantum metrology allows surpassing the standard quantum limit, but methods relying on squeezing require to know the orientation of the squeezed quadrature with respect to the signal. Here, instead, the authors propose a phase-insensitive Fock-state-based protocol, and demonstrate it using trapped ions.